Case Study: Implementation of Lean Logistics at Inversiones Karmont S.A.C for Enhancing Distribution Productivity - Deysi Llanos-Solorzano; Yenipher Dayana Barboza-Quispe; Ruben Felipe Vidal Endara (Engineering Proceedings)
The main objective of this research was the application of Lean Logistics philosophy to increase productivity in the distribution area. The methodological approach of this research was quantitative, applied in nature, with an explanatory level of study and an experimental design with a pre-experiment degree. With a sample of 179 orders for Confy Marco mattresses, the study was conducted as a pre- and post-test analysis. For the first part of this research, documentary review was used as the data collection technique, with the registration form used as the instrument. The second part of the research employed observation technique, with the structured observation form used as the instrument. The hypothesis test was conducted using the Student’s T-test, which yielded a significance of 0.000 (<0.05), leading to the rejection of the null hypothesis and acceptance of the alternative hypothesis. Productivity before implementation was 61%, and after implementation, it increased to 87%, demonstrating that the application of Lean Logistics improved the productivity of the distribution area at Inversiones Karmont.